FORMULASI MADU DAN GULA AREN TERHADAP KARAKTERISTIK ORGANOLEPTIK SNACK BAR KENARI (Canarium indicum) - Irfan Nababan; Syane Palijama; Sophia Grace Sipahelut (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Snack bars are practical and nutritious food products, yet most still use imported raw materials such as cane sugar. This study aimed to evaluate the effect of honey and palm sugar formulations as natural sweeteners on the organoleptic characteristics of canarium nuts (Canarium indicum L.)-based snack bars. Canarium nuts were selected as the raw material due to their high nutritional content, including fats, proteins, and bioactive compounds such as omega fatty acids and antioxidants. Honey and palm sugar were used as alternative natural sweeteners with lower calories and a lower glycemic index compared to cane sugar. This research employed a Completely Randomized Design (CRD) with five honey and palm sugar formulation treatments: P0 (0%:0%), P1 (2%:30%), P2 (4%:24%), P3 (6%:18%), and P4 (8%:12%). Each treatment was replicated twice. The observed parameters included organoleptic tests (taste, color, texture, and overall acceptability) involving 30 semi-trained panelists. Data were analyzed using ANOVA and Tukey's post-hoc test (α=0.05). The results showed that the honey and palm sugar formulations had a highly significant effect (P < 0.01) on the organoleptic characteristics of the snack bars. The best treatment was achieved with the formulation of 6% honey and 18% palm sugar (P3), which yielded the highest hedonic scores for taste (3.42), color (3.46), and overall acceptability (3.50). This formulation also produced a crispy texture (score 2.88) and a savory flavor preferred by the panelists. In conclusion, the combination of 6% honey and 18% palm sugar is the optimal formulation for producing canarium nut snack bars with the best organoleptic characteristics. This study recommends further exploration of concentration variations and chemical analyses to optimize product quality.